Testing for selection bias and moral hazard in private health insurance: Evidence from a mixed public‐private health system. (13th September 2022) - Afoakwah, Clifford; Byrnes, Joshua; Scuffham, Paul; Nghiem, Son
Abstract: Separating selection bias from moral hazard in private health insurance (PHI) markets has been a challenging task. We estimate selection bias and moral hazard in Australia's mixed public‐private health system, where PHI premiums are community‐rated rather than risk‐rated. Using longitudinal cohort data, with fine‐grained measures for medical services predominantly funded by PHI providers, we find consistent and robust estimates of advantageous selection among hospitalized cardiovascular disease (CVD) patients. Specifically, we show that in addition to their risk‐averse attributes, CVD patients who purchase PHI use fewer services that are not covered by PHI providers (e.g., general practitioners and emergency departments) and have fewer comorbidities. Finally, unlike previous studies, we show that ex‐post moral hazard exists in the use of specific "in‐hospital" medical services such as specialist and physician services, miscellaneous diagnostic procedures, and therapeutic treatments. From the perspective of PHI providers, the annual cost of moral hazard translates to a lower bound estimate of $707 per patient, equivalent to a 3.03% reduction in their annual profits.